1997
DOI: 10.1007/bf02291637
|View full text |Cite
|
Sign up to set email alerts
|

Nitrodihydropyrimidines (review)

Abstract: Published data on the production and chemical transformations of nitrodihydropyrimidines are reviewed. Examples of substances having high biological activity are given.The pyrimidine fragment is present in the molecules of a series of biologically active compounds, many of which have found use in medical practice (soporific, antiinflammatory, antitumor, and other products) [1, 2]. In this connection, great attention has recently been paid to derivatives of pyrimidine, including their hydrogenation products. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…When the reaction of the 1-(2-hydroxyphenyl)-2-nitroethanone 1 with various arylaldehydes 2a and urea 3 was conducted it was observed that the electron deficiency and nature of the substituents on the aromatic ring aldehydes effect the conversion rate; aromatic aldehydes having electron-withdrawing groups on the aromatic ring (Table 3, New and Efficient Catalyst for the Synthesis of Novel 5-Nitro-3,4-dihydropyrimidin-2(1H)-ones 283 entries 6,8,9) reacted faster than electron-donating groups (Table 3, entries 2, 11, 12). The synthesized compounds were characterized by spectroscopy analysis.…”
Section: General Procedures For the Synthesis Of Nitro Dihydropyrimidimentioning
confidence: 99%
See 3 more Smart Citations
“…When the reaction of the 1-(2-hydroxyphenyl)-2-nitroethanone 1 with various arylaldehydes 2a and urea 3 was conducted it was observed that the electron deficiency and nature of the substituents on the aromatic ring aldehydes effect the conversion rate; aromatic aldehydes having electron-withdrawing groups on the aromatic ring (Table 3, New and Efficient Catalyst for the Synthesis of Novel 5-Nitro-3,4-dihydropyrimidin-2(1H)-ones 283 entries 6,8,9) reacted faster than electron-donating groups (Table 3, entries 2, 11, 12). The synthesized compounds were characterized by spectroscopy analysis.…”
Section: General Procedures For the Synthesis Of Nitro Dihydropyrimidimentioning
confidence: 99%
“…However, the reaction carried out under microwave irradiation gave excellent yields (entry 4, 2). The yield of desired product 4a was moderate when methanol and ethanol was used as solvent (entry [5][6][7][8] and in this case product 4a was separated by column chromatography over silica gel using hexane/EtOAc (7:3) as an eluent.…”
Section: General Procedures For the Synthesis Of Nitro Dihydropyrimidimentioning
confidence: 99%
See 2 more Smart Citations
“…8 At the same time, it was shown that nitro derivatives of dihydropyrimidinones (IV) are Ca antagonists or agonists depending upon character and position of a substituent in the Ar group having low acute toxicity. 9 …”
mentioning
confidence: 97%